2013
DOI: 10.1016/j.chemosphere.2012.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of arsenic species in algae and freshwater plants of an extreme arid region in northern Chile, the Loa River Basin

Abstract: 11This study reports data on arsenic speciation in two green algae species (Cladophora sp. and 12 Chara sp.) and in five aquatic plants (Azolla sp., Myriophyllum aquaticum, Phylloscirpus cf. 30-One sample (Cladophora sp.) presented hyperaccumulation of As (11,000 mg As kg -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 34 publications
4
42
0
5
Order By: Relevance
“…Although our study was focused on arsenic, at concentrations currently occurring in some natural ponds (Pell et al 2013), most likely these animals are not exposed to a single heavy metal, which may influence in the rotifer response to these toxicants (Jara and Aránguiz-Acuña 2013). Ríos-Arana et al (2005) showed contrasting effects on induction of heat shock protein HSP60 by the rotifer Plationus patulus when was exposed to arsenic alone and to arsenic mixed with other heavy metals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our study was focused on arsenic, at concentrations currently occurring in some natural ponds (Pell et al 2013), most likely these animals are not exposed to a single heavy metal, which may influence in the rotifer response to these toxicants (Jara and Aránguiz-Acuña 2013). Ríos-Arana et al (2005) showed contrasting effects on induction of heat shock protein HSP60 by the rotifer Plationus patulus when was exposed to arsenic alone and to arsenic mixed with other heavy metals.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicant was incorporated into the treatments as As 2 O 3 because this is a compound commonly found in aerosols produced by copper smelters that is dispersed by air, contributing to the contamination of water bodies (Pell et al 2013). As 3?…”
Section: Preliminary Bioassaysmentioning
confidence: 99%
See 1 more Smart Citation
“…HG-AFS Millenium Excallibur (PS Analytical, UK) was used for total arsenic measurement in seawater. The chromatographic system, consisting of an Agilent 1200 LC quaternary pump equipped with an autosampler, was connected to an anion-exchange and cation-exchange column and guard- 55 column and coupled to an Agilent 7500ce ICP-MS (Agilent, Germany) equipped with Ari Mist HP nebulizer (Burgener, Canada). The chromatographic program, instrumental operating conditions of LC-ICP-MS and the arsenicals that can be separated with each chromatographic system are given in Table 1.…”
Section: Instruments and Apparatusmentioning
confidence: 99%
“…The same extraction method (water extraction) was applied in all cases in order to assure that the differences in the results are only attributable to the pre-treatment. We selected 55 C. mediterranea Sauvageau (heterokonphyta, fucales) because of its abundance, availability, environmental interest and arsenic content; specifically, we worked with the alga branches because they are deciduous structures that can completely regenerate from the stipe. As kg −1 , was used for quality control purposes in total arsenic determinations.…”
Section: Introductionmentioning
confidence: 99%